Optimización del sistema de distribución de agua potable en la Comunidad de Marsella - Calderón-Murillo, Pamela (Instituto Tecnológico de Costa Rica, 2007)
The main objective of this project is to establish the technical and feasible criteria necessary for the optimization process of Marsella`s Water-Distribution- System, a rural community located in La Venecia de San Carlos. For this purpose, a hydraulic and water-quality like analysis was undertaken for the whole system’s extension. Based on such analysis, corrective actions are expected to be taken in order to ensure the future continuity and correct operation of the system. At the present moment, the system exhibits various performance deficiencies. Furthermore, the construction of the main water conduction tunnel for the Toro III Hydroelectric Project has imposed a potential threat to the water-distribution-system’s continuity. There is a latent possibility that this tunnel might negatively impact, the system’s main water source. This project was carried out at the Instituto Costarricense de Electricidad (ICE), which has assumed the responsibility to guarantee the future continuity of the system. The assignment was undertaken in several stages, from the field characterization and data gathering to the analytical process and financial statement. A total compliance with the national legislation in accordance with all relevant institutions involved was ensured.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: Túnel; Análisis hidráulico; Proyecto hidroeléctrico toro lll; Impacto ambiental; Sistema de distribución